Comparison of Absorbed Dose in Plasticine Bolus and Silicone Rubber Bolus - Leony Chantika Leony; Viesca Fredilla Hanif; Eli Defira; Sri Oktamuliani Oktamuliani; Afdhal Muttaqin; Muhammad Ilyas (Universitas Sebelas Maret, 2022)
Bolus is a radiotherapy device used to increase the surface dose in the skin surface area when using electron or photon beams. The most commonly used bolus is a bolus made from plasticine, in addition to a plasticine bolus there is also a bolus made from silicone rubber which is currently being developed. This study aims to determine which bolus is more effectively used in radiotherapy, by comparing the absorbed dose, the value of Relative Electron Density (RED), and the transmission factor of each bolus. In this study, silicone rubber and plasticine boluses were made with dimensions of 12 cm x 12 cm, the variation of energy used in LINAC was 9 MeV and 12 MeV and the thickness variation of each bolus was 0.5 cm, 1.0 cm, 1, 5 cm and 2.0 cm. The RED value obtained from the plasticine bolus for a thickness of 0.5 cm is 0.837 g/cm3, a thickness of 1.0 cm is 1.011 g/cm3, a thickness of 1.5 cm is 1.06 g/cm3, and a thickness of 2.0 cm of 1.072 g/cm3, while for silicone rubber bolus for a thickness of 0.5 cm is 1.146 g/cm3, a thickness of 1.0 cm is 1.151 g/cm3, a thickness of 1.5 cm is 1.17 g/cm3, and a thickness of 1.5 cm is 1.17 g/cm3 2.0 cm is 1.193 g/cm3. From the results of the study for the RED value of each bolus, it can be concluded that the silicone rubber bolus has a RED value that is more consistent with the water density value compared to the plasticine bolus. Silicone rubber and plasticine boluses can also be said to be absorbent materials because the transmission factor value of both boluses is below 100%. From the results of the study, silicone rubber boluses were more able to reduce the range of absorbed doses compared to plasticine boluses.